The world of our little friends the ants - Harun, Yahya (Goodword Books Place of publication not identified, 2001)
World of Our Little Friends the Ants offers an engaging exploration of the fascinating lives of ants, uncovering their social structures, behaviors, and the vital role they play in nature$1 (Bs ecosystem.s